Binding of integration host factor (IHF) to the ilvGp1 promoter of the ilvGMEDA operon of Escherichia coli K12. - Pereira, R F (1988)
Crude extracts of Escherichia coli K-12 were found to bind DNA restriction fragments containing ilvGp1. Our analysis using a series of restriction fragments and a BamHI linker mutation indicate that a factor binds to ilvGp1 or adjacent to it. Analysis with mutant strains of E. coli K-12 and purified IHF indicate that IHF binds to ilvGp1. Furthermore, both analysis in vivo and in vitro indicate that IHF precludes transcription from ilvGp1.